2020
DOI: 10.1212/wnl.0000000000009559
|View full text |Cite
|
Sign up to set email alerts
|

Validation of serum neurofilaments as prognostic and potential pharmacodynamic biomarkers for ALS

Abstract: ObjectiveTo identify preferred neurofilament assays and clinically validate serum neurofilament light (NfL) and phosphorylated neurofilament heavy (pNfH) as prognostic and potential pharmacodynamic biomarkers relevant to amyotrophic lateral sclerosis (ALS) therapy development.MethodsIn this prospective, multicenter, longitudinal observational study of patients with ALS (n = 229), primary lateral sclerosis … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
152
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(178 citation statements)
references
References 30 publications
22
152
3
1
Order By: Relevance
“…In recent years, there has been strong evidence from independent groups, large cohorts of patients, and multicenter studies that neurofilament light chains are potentially valuable ALS biomarkers ( 3 , 5 13 , 21 , 23 ). Verde et al showed that serum NFL is increased in ALS compared to other conditions and can serve as a diagnostic and prognostic biomarker using ultrasensitive single-molecule array technology ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, there has been strong evidence from independent groups, large cohorts of patients, and multicenter studies that neurofilament light chains are potentially valuable ALS biomarkers ( 3 , 5 13 , 21 , 23 ). Verde et al showed that serum NFL is increased in ALS compared to other conditions and can serve as a diagnostic and prognostic biomarker using ultrasensitive single-molecule array technology ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a relatively large cohort of 190 ALS patients and 130 with other neurological diseases, Rossi et al confirmed that CSF NFL and p-NFH were valuable diagnostic and prognostic biomarkers in ALS ( 10 ). A prospective, multicenter, longitudinal study validated NfL values as prognostic biomarker for ALS, comparing serum and CSF NfL values ( 13 ). Tortelli et al found that CSF NFL levels were increased in ALS compared to other neurodegenerative disorders and peripheral neuropathies and were correlated with disease severity and progression ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In univariate regression models, NF levels retain a high hazard risk for death [57,70,81]. More importantly, in multivariate models encompassing all other known prognostic factors such as ALSFRS-r, site of onset, age at onset, weight loss, and respiratory measures, only serum NfL concentration and some clinical variable different from one study to another (FVC [90] age, baseline ALSFRS-R, ΔFRS [86]), resulted as independent predictors of survival [90,91]. Considering ALSFRS-R slope as the outcome, and taking into account baseline serum NfL and pNfH together with potential clinical predictors of prognosis (age, sex, C9ORF72 status, site of disease onset, baseline ALSFRS-R and ΔFRS), only progression rate resulted a meaningful clinical predictor.…”
Section: Nfs As Prognostic Biomarkers In Als and Other Mndsmentioning
confidence: 99%
“…Considering ALSFRS-R slope as the outcome, and taking into account baseline serum NfL and pNfH together with potential clinical predictors of prognosis (age, sex, C9ORF72 status, site of disease onset, baseline ALSFRS-R and ΔFRS), only progression rate resulted a meaningful clinical predictor. Nevertheless adding to the model baseline serum NfL, but not pNfH adds prognostic value not explainable otherwise (for every 1-point increase in log serum NfL level, the progression rate [92] is worsened by an additional 0.42 points/month [86]). Other studies supported the use of baseline serum or CSF NfL levels as an independent prognostic factor, with equal, if not superior value, of progression rate at diagnosis (delta-FS) [71], one of the most widely accepted clinical prognostic index computed at diagnosis [83].…”
Section: Nfs As Prognostic Biomarkers In Als and Other Mndsmentioning
confidence: 99%